An Alumina Toughened Zirconia Composite for Dental Implant Application: In Vivo Animal Results. (6th April 2015) - Schierano, Gianmario; Mussano, Federico; Faga, Maria Giulia; Menicucci, Giulio; Manzella, Carlo; Sabione, Cristian; Genova, Tullio; Degerfeld, Mitzy Mauthe von; Peirone, Bruno; Cassenti, Adele; Cassoni, Paola; Carossa, Stefano
Abstract : Ceramic materials are widely used for biomedical applications because of their remarkable biological and mechanical properties. Composites made of alumina and zirconia are particularly interesting owing to their higher toughness with respect to the monolithic materials. On this basis, the present study is focused on the in vivo behavior of alumina toughened zirconia (ATZ) dental implants treated with a hydrothermal process. A minipig model was implemented to assess the bone healing through histology and mRNA expression at different time points (8, 14, 28, and 56 days). The novel ATZ implant was compared to a titanium clinical standard. The implants were analyzed in terms of microstructure and surface roughness before in vivo tests. The most interesting result deals with a statistically significant higher digital histology index for ATZ implants with respect to titanium standard at 56 days, which is an unprecedented finding, to the authors' knowledge. Even if further investigations are needed before proposing the clinical use in humans, the tested material proved to be a promising candidate among the possible ceramic dental implants.